Dynamics of Adolescent Development from a Psychological Perspective and Its Implications for Islamic Religious Education at Al-Furqon Islamic Boarding School, Prabumulih - Nurwahida Nurwahida; Farah Nur Fadhilah; Ermis Suryana; Zulhijrah Zulhijrah (Journal of Educational Sciences, 2026)
Adolescence is a significant transitional developmental phase from childhood to adulthood, encompassing physical, psychological, intellectual, and social aspects. According to the Indonesian National Population and Family Planning Board (BKKBN), adolescence refers to individuals aged 10–24 years. Early and middle adolescence, which ranges from 10 to 16 years of age, is particularly relevant for discussion in relation to phenomena occurring in Islamic boarding schools at the junior and senior secondary levels, such as Pondok Pesantren Al-Furqon Prabumulih. This period is characterized by major changes as part of the process of self-recognition and self-understanding. This study focuses on how the character of adolescents or santri living within the pesantren environment is formed, both psychologically and educationally, as these factors serve as the primary influences on students’ development. The research employs a qualitative descriptive method, utilizing primary data sources and relevant literature, with observation techniques applied to the students of Pondok Pesantren Al-Furqon Prabumulih. The results indicate that the pesantren environment and educational practices significantly influence the formation of students’ personalities in emotional, social, moral, and intellectual dimensions. These influences play a crucial role in shaping the students’ future lives, both socially and intellectually.